(untitled) (Global Journal of Human-Social Science, 2019)
An economy centered on the use of information as a strategic resource adds value to products and services, demand from the business world for new business structures and innovative management strategies, based on knowledge management as the most important asset as individuals and organizations learn today becomes the competitive advantage that makes them effective in the market.